Pro CSS for High Traffic Websites - Kennedy, Antony; de Leon, Inayaili (Apress : Imprint: Apress, 2011)
Although web standards-based websites can scale effectively-and basic CSS will give you basic results-there are considerations and obstacles that high traffic websites must face to keep your development and hosting costs to a minimum. There are many tips and tricks, as well as down-to-earth best practice information, to make sure that everything runs quickly and efficiently with the minimum amount of fuss or developer intervention. Targeted at "high traffic" websites-those receiving over 10,000 unique visitors a day-Pro CSS for High Traffic Websites gives you inside information from the professionals on how to get the most out of your web development team.  The book covers the development processes required to smoothly set up an easy-to-maintain CSS framework across a large-volume website and to keep the code reusable and modular. It also looks at the business challenges of keeping branding consistent across a major website and sustaining performance at a premium level through traffic spikes and across all browsers. Defensive coding is considered for sites with third-party code or advertising requirements. It also covers keeping CSS accessible for all viewers, and examines some advanced dynamic CSS techniques.